Inspection - Hole shape optimization of a lower wing panel based on geomatric boundary shapes / Wahyu Kuntjoro and Zon S. Hernedhi - Kuntjoro, Wahyu; Hernedhi, Zon S. (UPENA, 2004)
Most structural design optimization jobs deal with finding the optimum size of structural components. Non-linear mathematical programming techniques are normally used to optimize this sort of problems. Some problems need not only optimum component size but also optimum shapes. Change of shape can be dictated by shape basis vectors, which define grid coordinate changes. As change of shape relates directly to change of geometry, the rules of geometric variation need to be set up which in this case is the variation of geometric boundary shapes. Change of boundary shape will alter the overall shape of the continuum. With the rule of geometric shape change been set-up, the optimization is carried out employing non-linear mathematical programming optimization. This paper presents an optimization of an inspection holes of IPTN CN-235 lower wing panel. It is required to have an optimum shape of the inspection hole and the dimensions of surrounding components. The wing itself was loaded by its critical design cases. Shape basis vectors were defined through geometric boundary shapes. Optimization was performed using MSC NASTRAN optimization design software.